THE INFLUENCE OF ENTREPRENEURIAL MARKETING ON MARKETING PERFORMANCE THROUGH DIGITAL MARKETING CAPABILITIES IN THE NEW NORMAL ERA ON MICRO SMALL AND MEDIUM ENTERPRISES IN PALU, CENTRAL SULAWESI - Ihksan, Ihksan; Zahara, Zakiyah; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research intends to determine the influence of Entrepreneurial Marketing through Digital Marketing Capabilities on Marketing Performance in the New Normal era for MSMEs in Palu, Central Sulawesi. Explanatory research method was conducted. The types and sources of data used was primary data through distributing questionnaires to 197 respondents who became the sample of this research. The sampling technique used was the Yamane and Isaac formula. Hypothesis testing used was path analysis with Smart-PLS software. The results show that Entrepreneurial Marketing through Digital Marketing Capabilities has a positive but not significant influence on Marketing Performance in the new normal era for MSMEs in Palu, Central Sulawesi. Keywords: Entrepreneurial Marketing, Digital Marketing Capabilities, Marketing Performance, Micro Small and Medium Enterprises